PENGETAHUAN PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DENGAN PERANNYA DALAM PENCEGAHAN STUNTING - Ni Made Darmiyanti (Jurnal Gema Keperawatan, 2019)
Knowledge and the Role of PKK in the Prevention of Stunting.The purpose of this research is to find out the relationship between knowledge and the role of PKK in stunting prevention in Manggis Village, Karangasem Regency in 2019.The study design uses the correlation method, located in Manggis Village, which uses research subjects from PKK mothers in Manggis Village with a population of 450 people, and a sample size of 45 people.The results of this study are, most (55.6%) knowledge of research subjects in the category of inadequate, most (71.2%) the role of research subjects in preventing stunting in the category of lack. There is a relationship between knowledge about stunting and the role of the PKK in preventing stunting in Manggis Village in 2019.